The only child, birth order and educational outcomes - Yehui Lao; Zhiqiang Dong (Kiel Institute for the World Economy (IfW), 2019)
The one-child policy was implemented in September 1980 and abolished in late 2015. With this change in the demographic policy, the fertility decision of families also changed. Such decisions can result in an increase in the number of siblings in a family. Individuals' educational outcomes may be affected by a change in their parents' fertility decision. The objective of this paper is to provide evidence of the difference of educational outcomes between the only child and the first born. The authors try to estimate the change of educational outcomes when the only child of a family turns to the first born of a family. Moreover, they estimate different channels to interpret these effects. They employ the dataset of China Education Panel data in this paper. In the part of mechanism check, the Sobel-Good test is used for checking the mediation effects of different channels. They found the only child has significant higher educational outcomes comparing to a child who has siblings. Furthermore, the middle child has the lowest educational outcomes of a family. The last born has higher educational outcomes than his or her siblings. To explain these effects, the authors use three channels to interpret: (1) money resource, (2) parenting time, and (3) closeness of parent-child relationships. The policy implication is to help the policymaker estimate and predict the impact of the new demographic policy.
Keywords: I20; J13; 330; only child; birth orders; educational outcomes